Impacts of roads and trails on floral diversity and structure of Ganga-Choti forest in Kashmir Himalayas - Shaheen, Hamayun; Riffat, Amra; Salik, Maria; Firdous, Syeda Sadiqa (BOSQUE, 2018)
Roads and trails bring deteriorating changes in the structure and composition of forests. The present study investigated the impact of roads and trails on floral diversity and structure of Ganga Choti forest, Kashmir. Phytosociological attributes using systematic quadrate sampling were recorded and analyzed using multivariate ordination techniques including Principal Component Analysis and Cluster Analysis. The total number of species found in the area was 101 belonging to 47 plant families. The dominant family was Poaceae followed by Labiateae, Asteraceae and Rosaceae. The dominant species of the area included Pinus wallichiana, Abies pindrow, Viburnum grandiflorum, Sarcococca saligna, Poa alpina, Fragaria nubicola, Onychium japonicum and Poa pratensis. The dominant life form was Hemicryptophyte (31.68 %), whereas leaf spectra class was Microphyll (30.69 %). The average diversity value was 3.39 with a maximum of 3.71 at the control site and 3.08 at the disturbed site. Average tree density was 505/ha with a maximum of 680/ha at the control site and a minimum of 330/ha at the disturbed site. Intense deforestation was indicated by a stump density value of 330/ha. Results revealed that roads and trails have adversely affected the composition and structure of vegetation with high pressure on keystone tree species. Disturbed sites showed lower values of diversity indices, species richness and regeneration synchronized with high deforestation, overgrazing, erosion and increased frequency of invasive species. The study area needs immediate attention of the management for conservation of local forests by minimizing the impacts of roads and trails.